Human Endogenous Retroviral Envelope Protein Syncytin-1 and Inflammatory Abnormalities in Neuropsychological Diseases - Wang, Xiuling; Huang, Jin; Zhu, Fan (Frontiers in Psychiatry, 2018)
Human endogenous retroviruses (HERVs) comprise approximately 8% of the human genome. Recent studies have considered HERVs as potential pathogenic factors. The majority of HERV genes are mutated and not capable of encoding functional proteins; regardless, some HERV genes, such as HERV-W envelope (env) glycoprotein, are known to have intact open reading frames. The HERV-W element on 7q21.2, which encodes a protein referred to as Syncytin-1, participates in human placental morphogenesis and can activate a pro-inflammatory and autoimmune cascade. Neuropsychological disorders are typically linked to inflammatory abnormalities. In this study, we review that Syncytin-1 has been increasingly involved in the development of neuropsychological disorders, such as schizophrenia and multiple sclerosis (MS). This study also presents inflammation imbalances in schizophrenia and MS. More importantly, we discuss the potential role and molecular mechanisms by which Syncytin-1 regulates inflammatory abnormalities in neuropsychological diseases. In summary, Syncytin-1 activity may represent a novel molecular pathogenic mechanism in neuropyschological diseases, such as schizophrenia and MS.